2017
DOI: 10.1002/smll.201603591
|View full text |Cite
|
Sign up to set email alerts
|

Coaggregation of κ‐Casein and β‐Lactoglobulin Produces Morphologically Distinct Amyloid Fibrils

Abstract: The unfolding, misfolding, and aggregation of proteins lead to a variety of structural species. One form is the amyloid fibril, a highly aligned, stable, nanofibrillar structure composed of β-sheets running perpendicular to the fibril axis. β-Lactoglobulin (β-Lg) and κ-casein (κ-CN) are two milk proteins that not only individually form amyloid fibrillar aggregates, but can also coaggregate under environmental stress conditions such as elevated temperature. The aggregation between β-Lg and κ-CN is proposed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…These levels further increase during heating (Chevalier & Kelly, ). Noteworthy is that isolated β‐LG and κ‐casein co‐aggregate into AFs during heating at 94 °C and pH 6.7 for 1 h. Even though these two proteins are structurally unrelated, they have sufficient sequence similarity which allows them to co‐fibrillate (Raynes, Day, Crepin, Horrocks, & Carver, ). While β‐casein inhibits fibril formation of β‐LG during heating at temperatures exceeding 75 °C at neutral pH, it does not prevent fibrillation during heating at 80 °C and pH 2.0.…”
Section: Bovine Milk Proteinsmentioning
confidence: 99%
“…These levels further increase during heating (Chevalier & Kelly, ). Noteworthy is that isolated β‐LG and κ‐casein co‐aggregate into AFs during heating at 94 °C and pH 6.7 for 1 h. Even though these two proteins are structurally unrelated, they have sufficient sequence similarity which allows them to co‐fibrillate (Raynes, Day, Crepin, Horrocks, & Carver, ). While β‐casein inhibits fibril formation of β‐LG during heating at temperatures exceeding 75 °C at neutral pH, it does not prevent fibrillation during heating at 80 °C and pH 2.0.…”
Section: Bovine Milk Proteinsmentioning
confidence: 99%
“…At higher storage temperatures, many chemical and physical changes occur to the milk, such as reduced serum calcium and phosphate levels and reduced ionic calcium levels (Holt, 1985), a reduction in casein micelle size (Anema, Lowe, & Lee, 2004) and a reduction in serum-phase casein levels (Dalgleish & Law, 1988), all of which may that may help retard the gelation or decrease gel volume when milk is stored at higher temperatures. Relatively recent reports have suggested that age gelation of UHT milk was a consequence of the formation of amyloid-like fibrils during the storage of milk, with the fibrils being composed of (dissociated) κ-casein and β-lactoglobulin (Holt, Carver, Ecroyd, & Thorn, 2013;Raynes, Day, Crepin, Horrocks, & Carver, 2017). This hypothesis was derived from lab-scale experiments using purified κ-casein and β-lactoglobulin solutions in a phosphate buffer, with the samples heated at approximately 100°C for 1 hr to form fibrils (Raynes et al, 2017).…”
Section: Age Gelation Through Physico-chemical Changes In the Milkmentioning
confidence: 99%
“…In addition, the heating conditions used to form the fibrils are considerably more extreme than those encountered during typical UHT processing of milk. In-can sterilized milk, which may have experienced heating conditions of approximately 120°C/20 min (Harwalkar, 1982(Harwalkar, , 1992, has heat loads more comparable to those used in the study of Raynes et al (2017), but these sterilized milk samples have a lower propensity to gel during storage than UHT milk (Harwalkar, 1982(Harwalkar, , 1992Nieuwenhuijse & van Boekel, 2003). To date, there is no evidence to show that amyloid-like fibrils are formed in UHT milk during storage.…”
Section: Age Gelation Through Physico-chemical Changes In the Milkmentioning
confidence: 99%
“…Gad m 1 amyloids are formed by the polymerization of the intermotif linker regions and cause the amplification of IgE binding 25,29,30 . This sequence and concentration-dependent conformational transition are not unique to this β-PV, having been described for a large number of proteins, some of which, such as β-lactoglobulin (Bos d 5), ovalbumin (Gal d 2) and κ-casein (Bos d 8), are food allergens 31,32 . Commonly consumed fish are restricted to a few orders, including Clupeiformes (herring, sardine, and anchovy), Cypriniformes (carp), Gadiformes (cod, pollock, and hake), Perciformes (perch, snapper, tuna, mackerel, and tilapia), Pleuronectiformes (sole and whiff), and Salmoniformes (salmon, trout, and whitefish) 33,34 .…”
Section: Introductionmentioning
confidence: 92%